Unbearable lightness a story of loss and gain - De Rossi, Portia 1973- (Atria Books, 2010)
Known for her roles on the hit TV shows "Ally McBeal" and "Arrested Development," de Rossi delivers a revelatory and searing account of the years she spent secretly suffering from anorexia and bulimia, all the while living under the glare of Hollywood's bright lights.